Ion- and electron-acoustic solitons and double layers in multi-component space plasmas - Lakhina, G. S.; Singh, S. V.; Kakad, Amar (My University, 2011)
A general model for the ion- and electron-acoustic solitons and double layers in a multi-component unmagnetized plasma consisting of background electrons, counter-streaming electron beams and ions is discussed. The model is based on the multi-fluid equations and the Poisson equation, and uses the Sagdeev pseudo-potential techniques. For identical counter-streaming electron beams and depending upon the plasma parameters, three types of solutions, namely, ion-acoustic, slow and fast electron-acoustic soliton/double layer, are possible. Generally, the ion acoustic solitons have positive potentials, slow-electron acoustic solitons have negative potentials and fast electron-acoustic solitons and double layers can have either positive or negative potentials depending on the core electron density. As beam speed is increased, first ion-acoustic and then slow electron-acoustic solitons disappear. At large beam speed, only fast electron-acoustic solitons/double layers survive. The results may be relevant to the observations of the electrostatic solitary waves (ESWs) observed in the Earth’s magnetosphere.
Keywords: Electrostatic solitary waves; Solitons; Nonlinear ion- and electron-acoustic waves; Space plasmas; Sagdeev pseudo-potential techniques; Poisson equation; Multi-fluid equations; Magnetosphere